Songbirds use scent cues to relocate to feeding sites after displacement: An experiment in great tits (Parus major) - Mahr, Katharina; Nowack, Linda; Knauer, Felix; Hoi, Herbert (Frontiers in Ecology and Evolution, 2022)
Air-borne chemicals are highly abundant sensory cues and their use in navigation might be one of the major evolutionary mechanisms explaining the development of olfaction in animals. Despite solid evidence for the importance of olfaction in avian life (e.g., foraging or mating), the importance of chemical cues in avian orientation remains controversial. In particular, songbirds are sorely neglected models, despite their remarkable orientation skills. Here we show that great tits (Parus major) require olfactory cues to orientate towards winter-feeding sites within their home range after displacement. Birds that received an olfaction-depriving treatment were impaired in homing. However, the return rates between olfaction-deprived and control individuals did not differ. Birds with decreased perception of olfactory cues required more time to return to the winter feeding sites. This effect became apparent when the distance between the releasing and capture sites was greater. Our results indicate that even in a familiar environment with possible visual landmarks, scent cues might serve as an important source of information for orientation.